Some problems of characterization of a solid surface via the surface free energy changes - Emil Chibowski (Adsorption Science & Technology)
During the processes occurring at a solid surface, the changes in the surface free energy take place. The knowledge about surface free energy is very helpful for understanding the processes taking place on the surface. However, experimental determination of solid surface free energy is still not a fully solved problem. In this paper, some problems dealing with calculation of solid surface free energy from contact angle are discussed based on literature values of advancing and receding contact angles measured on four different fluoropolymers surface. The four approaches most often used for the calculation are described and especial focus on the approach in which both the advancing and receding contact angles is paid. It is concluded that using probing liquids the absolute value of solid surface free energy cannot be determined. However, the determined apparent values of the energy are very helpful to understand the conditions necessary for a given process to occur.